2013
DOI: 10.3174/ajnr.a3611
|View full text |Cite
|
Sign up to set email alerts
|

Right Insular Atrophy in Neurocardiogenic Syncope: A Volumetric MRI Study

Abstract: BACKGROUND AND PURPOSE:Alterations in the central autonomic network are hypothesized to play a role in the pathophysiologic mechanism underlying neurocardiogenic syncope; however, few data are available regarding the structural changes of the brain in this condition. We used voxel-based morphometry and regional volumetry to identify possible neuroanatomic correlates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Several findings support the notion that cortical thinning may precede the onset of symptoms and induce OH. First, two previous VBM studies investigated the brain volume of patients with OI, especially vasovagal syncope (VVS), and they demonstrated right insular or brainstem atrophy in patients with VVS [6,8]. They suggested that the brain atrophy of the insular cortex or brainstem might decrease the sympathetic activity and lead to VVS [8].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several findings support the notion that cortical thinning may precede the onset of symptoms and induce OH. First, two previous VBM studies investigated the brain volume of patients with OI, especially vasovagal syncope (VVS), and they demonstrated right insular or brainstem atrophy in patients with VVS [6,8]. They suggested that the brain atrophy of the insular cortex or brainstem might decrease the sympathetic activity and lead to VVS [8].…”
Section: Discussionmentioning
confidence: 99%
“…First, two previous VBM studies investigated the brain volume of patients with OI, especially vasovagal syncope (VVS), and they demonstrated right insular or brainstem atrophy in patients with VVS [6,8]. They suggested that the brain atrophy of the insular cortex or brainstem might decrease the sympathetic activity and lead to VVS [8]. Our present study also revealed cortical thinning in the orbitofrontal, post-central, and inferior temporal cortexes, which are areas known to be associated with the regulation of the autonomic nervous systems, and these findings consistently supported the susceptibility to OH in patients with OH [13,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations